Impact of pharmaceutical counseling in minor health problems in rural Portugal - Coelho, Raquel B. (2014)
"Objectives: The objectives of this study were to determine the prevalence of self-medication and to evaluate the clinical impact of pharmaceutical counseling. Methods: A cross-sectional study was used with a prospective component, the latter to evaluate the impact of pharmaceutical counseling . The study was conducted in a rural community pharmacy for 14 consecutive days in December 2012, recruiting all individuals who agreed to participate and met the eligibility criteria. During a facetoface direct interview demographic and clinical characteristics of patients were registered, followed by a pharmaceutical intervention, which consisted of evaluating the symptoms, selecting the most appropriate nonprescription medicine (NPM) available and advising the patient on pharmacologic and non-pharmacologic measures, all according to established protocols for minor health problems. When appropriate, the patient was referred to a medical appointment. One week later, the clinical outcome of such intervention was measured by asking the patients about the resolution of their minor health problems. Results: Data from 298 patients were analyzed, the majority being female (60.1%) with an average age of 44.84 years (SD=22.41). Respiratory problems were the most frequent (n=78; 26.2%) and respiratory tract medication was the most frequently indicated (n= 77; 27.8%). The observed prevalence of self-medication was 40.7%. Of the 271 patients’ beneficiaries of pharmaceutical counseling, 86.8% had their minor health problems solved after one week (ranging from 77.5% to 88.2% according to a sensibility analysis for drop-outs). Conclusions: This work is important as it demonstrates the beneficial impact of pharmaceutical counseling, a very relevant area for the pharmacist and where literature is particularly scarce."